The The Influence of Perceived Convenience and Service Quality on Customer Loyalty (A Study at the Brilink Agent Bio Energy 2 Sidoarjo) - Devi Putri Pratama; Budi Prabowo (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2025)
Banks are business entities that collect funds from the public in the form of savings and then distribute them to the public in the form of credit and/or other forms to improve people's living standards. The development of the digital world means that the banking world does not want to lose promising business opportunities. The Brilink agent is one of BRI's breakthroughs in educating the public to know basic knowledge about financial management using banking products and services. BRILink agents as an extension of Bank BRI provide various conveniences for people in remote areas, coupled with good service quality, it is hoped that they will be able to help the current needs of the community. BRILink not only provides operational efficiency benefits but also makes it easier for BRI customers and non-BRI customers to make transactions with BRI. This research examines how perceptions of comfort and service quality influence customer loyalty through customer satisfaction as an intervening variable (study at the Brilink Bio Energi 2 Sidoarjo agent). This research is a type of quantitative research. The population used in this research was all customers of the BRILink Bio Energi 2 Sidoarjo Agent. In determining the sample, the Accidental Sampling technique was used, namely the random sampling method. Respondents will be randomly selected to be samples in this research. Data analysis was carried out using the SPSS version 25 program with the help of path analysis as a hypothesis test. Research findings show that perceptions of convenience and service quality directly have a positive and significant effect on customer loyalty through customer satisfaction.